IMPLEMENTASI PERATURAN WALIKOTA NO.41 TAHUN 2015 TENTANG PENCEGAHAN DAN PENANGGULANGAN HIV AIDS DI KOTA SINGKAWANG TAHUN 2016 - Yulia Farahdini; Laksono Trisnantoro; Yodi Mahendradhata (Journal of Health Service Management, 2019)
Background: Singkawang is a city in West Kalimantan with the second highest number of HIV in West Kalimantan in 2012. To cope with this, then in November 2015, was issued on Mayor Regulation No. 41 Year 2015 on Prevention and Control of HIV AIDS. Objective: To determine the implementation of Singkawang Mayor Regulation No. 41 Year 2015 on Prevention and Control of HIV AIDS in Singkawang. Methods: The study was a descriptive study with a qualitative method by using a single case study design. The way of data collection is done by observation, interview and document study. Analysis techniques used were the analysis of the content (content analysis). Results: In the aspect of the implementation process, in terms of planning, has been carried out properly. However, not all relevant agencies involved in the planning. In terms of acceptability and appropriateness, Mayor Regulation No. 41 Year 2015 has been quite good. However, the constraints of the implementation is the problem of lack of funds and lack of training for agencies outside the health sector. Conclusion: In the Mayor’s efforts to implement Regulation Singkawang Singkawang Goverment expected to develop aspects of equitable funding and training for all agencies to carry out prevention and control of HIV according to Singkawang Mayor Regulation No. 41 2015.